Use of gentamicin-collagen sponges prior to sternal closure may lower the risk of sternal wound infection: a single center experience - Čanádyová, Júlia; Kurfirst, Vojtěch; Mokráček, Aleš (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Despite improvements in prophylactic strategies, sternal wound infection following cardiac surgery still remains a significant complication, associated with prolonged hospitalization, high costs, patient discomfort and significant mortality. The aim of this study was to evaluate whether the local application of collagen-gentamicin sponges (GMCS) placed between the sternal halves before closure may decrease the incidence of median sternotomy wound infection. Between April 2008 and December 2009, 236 patients were enrolled in the study. We compared 120 consecutive patients whose wounds were closed with the use of collagen-gentamicin sponges (GMCS group) with 116 consecutive patients whose wounds were closed without the use of local antibiotic prophylaxis (non-GMCS group). All postoperative sternal wound complications were referred back to the Cardiac Surgery Department. The three-month incidence of any wound healing complication was the main outcome criterion. The use of GMCS significantly reduced the rate of wound infection to 8.3% vs. 19.8% in the non-GMCS group (p < 0.0197). The patients whose wounds were closed without the use of local antibiotic prophylaxis had a higher risk of infection-related complications compared with patients in whom GMCS were used prior to closure (OR = 2.95, 95% CI: 1.29-6.71). Our study demonstrated the benefit of using GMC in reducing the rate of sternal wound infection.